PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BALAI PENGEMBANGAN PENDIDIKAN KEJURUAN (BP DIKJUR) SEMARANG - Arief Dermawan, 09.05.51.0018; Wanuri, Wanuri (Students Journal of Economic and Management, 2013)
This study aims to examine and analyze the effect of leadership style, communication and organizational culture on employee performance Vocational Education Training Center (BP DIKJUR). The data was collected through questionnaires and conducted at 75 Hall employee development Vocational Education (BP DIKJUR). In this case, the study is the employess at the office BP DIKJUR Semarang consisting of 75 people, also called census. Mechanical testing data used in this study include the validity test using the Kaiser-Mayer Olkin Measure of Sampling Adquecy (KMO) and Loading factor. The result showed that the value of Kaiser-Mayer Olkin Measure of Sampling Adquecy (KMO) qualified for further analysis analyzes use traditional multiple regression analysis to explain the relationship between these variables. The result is the result suggests the hypothesis that leadership style has positive and significant impact on employee performance, while communication does not affect employee performance and organizational culture positive and significant influence on employee performance.Key words : leadership styles, communication and organizational culture on employee performance